Fly ash utilization for methane production improvement from co-digestion between cow dung and Pennisetum Purpureum - Vanatpornratt Sawasdee (Elsevier, 2021)
This research aimed to study fly ash utilization for methane production improvement from co-digestion between cow dung and Pennisetum Purpureum. Co-digestion conditions were variable in three conditions consisting of 0 (Control condition), 5, and 10 g L− fly ash, respectively. Fly ash from a biomass powerplant included several elements that were trace elements for microorganisms in the methane production system, such as calcium (Ca), phosphorus (P), potassium (K), and iron (Fe). Phosphorus is a component of nucleic acid in the methane production system obtained from fly ash. Potassium, calcium, and iron are elements of coenzymes in microorganism mechanisms in biogas production. Thus, fly ash can be improved methane production from an anaerobic digestion system. The 5, and 10 g L−1 fly ash conditions were obtained using 54.14% and 48.68%, respectively. The co-digestion with 5 g L−1 fly ash addition can increase the percentage of methane production. The kinetic methane production in the control condition, 5, and 10 g L−1 fly ash presented Hmax85, 185, and 165 mL, respectively. Rmaxin the control condition, 5, and 10 g L−1 fly ash presented 30, 30, and 22 mL hr −1, respectively. The highest kinetic methane production (Hmaxand Rmax) was presented in the 5 g L−1 fly ash condition. Therefore, the suitable condition for fly ash utilization was 5 g L−1 fly ash. As a result, this research can be applied for waste utilization and management in industry and slaughterhouses. Finally, the benefit of this research was related to BCG model that increased waste utilization and valuable from industry and community, resulting in environmental sustainability.